Electrochemically-driven solid oxide tubular membrane reactor for efficient separation of oxygen and argon - Yuanhui Tang; Yutao Hu; Sisi Wen; Song Lei; Yakai Lin; Li Ding; Haihui Wang (Journal of Membrane Science Letters)
The high purity of Ar is crucial for industrial applications such as steel production, welding, and laboratory use, while the similar physical properties of O2 and Ar make their efficient separation challenging. Existing technologies, such as cryogenic distillation and pressure swing adsorption, are well-established and widely utilized but are hindered by high energy consumption, operational complexity, or limited efficiency. Inspired by the principle that O2 can permeate through the electrolyte as oxygen ions (O2-) in a solid oxide electrolysis cell, for the first time, this study designed and developed an electrochemically-driven tubular inorganic membrane reactor to separate O2/Ar mixtures, achieving high-purity Ar (≥99.99 %). The tubular membrane reactor featured an anode/electrolyte/cathode sandwich structure, offering a compact design particularly suited for gas separation. The reactor employs Ce0.1Gd0.9O2-x (GDC) as the electrolyte, while GDC and Ba0.9Co0.7Fe0.3Nb0.1O3-x are used as the electrode materials. The resulting membrane reactor was compact, defect-free, and capable of producing Ar with a purity of 99.99 %. Additionally, under a constant total current of 0.75 A and an operating temperature of 800 °C, the membrane reactor demonstrated stable performance for over 130 hours, maintaining a Faradaic efficiency exceeding 95 %. This study anticipates that the membrane reactor can serve as an effective and practical solution for separating O2/Ar mixtures, particularly at low O2 partial pressures.